Development and Application of Fruit Color-Related Expressed Sequence Tag-Simple Sequence Repeat Markers in Abelmoschus esculentus on the Basis of Transcriptome Sequencing - An, Xia; Luo, Xiahong; Liu, Tingting; Li, Wenlue; Zou, Lina (Frontiers in Plant Science, 2022)
Abelmoschus esculentus is a medicinal and edible plant that contains large amounts of active ingredients, including anthocyanins, polysaccharides, flavonoids, and terpenoids. However, because of a relative lack of molecular research, there are few molecular markers applicable for this plant species. In this study, on the basis of A. esculentus fruit color-related transcriptome sequencing data, we analyzed the patterns of simple sequence repeats (SSRs) in differentially expressed genes (DEGs) and revealed the biological processes and metabolic pathways associated with the related genes. We also designed primers for SSR loci to develop SSR molecular markers. Primers were synthesized using a DEG associated with a protein–protein interaction network. Polymorphic SSR markers were screened for the subsequent examination of A. esculentus germplasm resources and fruit color association analysis. The results indicated that 24.98% of the unigenes contained SSR motifs. Single-base (mononucleotide) repeats were the main SSRs, followed by trinucleotide and dinucleotide repeats. We selected 47 EST-SSR primer pairs for the genotyping of 153 A. esculentus varieties/lines. We ultimately obtained 21 EST-SSR markers suitable for genotyping. A generalized linear model-based association analysis detected two EST-SSR markers significantly associated with A. esculentus fruit color. In conclusion, several EST-SSR and SSR molecular markers in A. esculentus were developed in this study. The fruit color-associated markers may be useful for the molecular marker-assisted breeding of new A. esculentus varieties.